Kajian Psikologis Perwatakan Tokoh Novel pada Sebuah Kapal Karya Nh. Dini dan Implikasinya dalam Pengajaran Sastra di SMP - Singal, Umy V.E (Bahasantodea, 2024)
The research aimed to describe the psychological aspects of the character in the novel Pada Sebuah Kapal (PSK) and their implications of literature teaching in junior high students. This research was a descriptive research using character psychoanalysis and psychology approach with descriptive methods and strategies of content analysis. The research procedure conducted by step of procurement of data through the determination of the unit of analysis, then the data recording process of inference and analysis. Data analysis was carried out through the following activities: (1) reducing the data, (2) study the data, (3) verification of the data, (4) checks the validity of the data through researchers perseverance technique. The results of research showed the evidence that: (1) there were two character figures depicted in PSK novel such as flat dispositive (Flat character) and round dispositive (round character), (2) the psychological aspects were revealed in PSK novel that character figures was influenced by childhood and firmly held view of life, selfish and rude character affects the pair life, (3) the behavior of children who were too spoiled would have a negative impact, causing the attitude and behavior of the selfish and rude. The bad temper carried the psychological burden, and (4) the content of PSK novel charge was mostly a reflection of the author's life experience, Nh. Dini. The results of the research have implications for literature teaching in junior high school. Proved that the PSK novel contained the elements of beauty (dulce) and useful (utile) therefore PSK novel deserved to be one choice for junior high school students in studying literature. Through knowledge of the nature of the character in PSK novel, the students could learn a person's personality as one of the competencies that were able to develop a personality and add insight into humanity involving a core element of literary appreciation namely cognitive, emotive and evaluative. In this case, it could enhance students' appreciation of novel.